A novel (targeted) kinesio taping application on chronic low back pain: Randomized clinical trial. - María Lourdes Peñalver-Barrios; Juan Francisco Lisón; Javier Ballester-Salvador; Julia Schmitt; Aida Ezzedinne-Angulo; María Dolores Arguisuelas; Julio Doménech (PLoS ONE)
The aim of the present clinical trial is to evaluate the efficacy of kinesio taping on patients with chronic low back pain, when the exploration identifies skin/fascia mobilization as a factor that could modify the treatment effect. This study is a randomized controlled trial with intention-to-treat analysis. Sixty-two participants with chronic low back pain were therefore recruited from a tertiary referral hospital. Targeted kinesio taping, according to skin/fascia mobility exploration, was applied in the experimental group (17 female/13 male; 49.47 ± 11.15 years) once a week for four sessions. The control group (17 female/14 male; 48.87 ± 9.09 years) underwent a placebo taping application. At post-treatment time there was a statistically significant reduction both in disability (Roland-Morris Disability Questionnaire) and pain (Numeric Pain Rating Scale) in the experimental group (disability: -2.88, 95% confidence interval [CI] -4.56 to -1.21, P < .001; pain: -1.58, 95% CI -2.67 to -0.54 P = .001) and the control group (disability: -1.82, 95% CI -3.46 to -0.17 P = .025; pain: -1.30, 95% CI -2.32 to -0.28 P = .008). However, at six months, these changes only remained significant in the experimental group (disability: -2.95, 95% CI -4.72 to -1.18, P < .001; pain: -1.06, 95% CI -2.07 to -0.04, P < .05). As a conclusion, the application of targeted kinesio taping produced a significant reduction in pain and disability, at 4 weeks and at 6 moths follow-up, although there were no differences between groups at any measurement time point.